The Intersection of Power and Gender: Examining the Relationship of Empowerment and Gender-Unequal Norms Among Young Adolescents in Kinshasa, Drc - Maddaleno-Herrera, M (Elsevier Inc., 2021)
Purpose: To examine how perceptions of gender norms and expressions of empowerment are related among disadvantaged young adolescent boys and girls in Kinshasa, DRC. Methods: We included data from 2,610 adolescent boys and girls between 10 and 14 years old. We examined correlations between three dimensions of perceived gender norms (a sexual double standard, gender stereotypical roles, and gender stereotypical traits) and two domains of agency (voice and decision-making), overall and by sex. We conducted sex-stratified simple and multivariable linear regression models to assess these associations, adjusting for sociodemographic factors. We also tested for differences in the association between gender norm perceptions and agency by sex. Results: Correlations between gender norm perceptions and agency scores were low (under 0.15). Among boys, greater perception of a sexual double standard was related to more voice (p=0.001) and more decision-making power (p=0.008). Similar patterns were observed among girls for the relationship between sexual double standard and voice (p≤.001), but not for decision-making. Increased perceptions of gender stereotypical traits were related to more voice among girls (p≤.001), while conversely girls who perceived greater gender stereotypical roles had less decision-making power (p=0.010). Conclusions: This study demonstrated that gender norm perceptions and agency are distinct but related constructs. Interventions aimed to promote gender equality must consider gender unequal norms and gender-unequal divisions of power as important but different dynamics. © 2021 Society for Adolescent Health and Medicine